Effects of robotic and laparoscopic-assisted surgery on lymph node dissection and quality of life in the upper third of gastric cancer: A retrospective cohort study based on propensity score matching - Fu, Jingxiao; Li, Yi; Liu, Xuechao; Jiao, Xuelong; Qu, Hongyu; Wang, Yuhao; Niu, Zhaojian (Frontiers in Surgery, 2023)
Objective: The objective of this study was compare the effects of robot-assisted and laparoscopic-assisted surgery on lymph node dissection and quality of life in upper third gastric cancer patients undergoing radical total gastrectomy. Methods: The clinical and follow-up data of 409 patients with upper one-third gastric cancer who underwent total gastrectomy from July 2016 to May 2021 were enrolled. The patients were divided into a robotic group (n=106) and a laparoscopic group (n=303). Age, sex, body mass index, American Society of Anesthesiologists score, tumor size and location, pathological type, cT, cN, and cTNM were adjusted to offset selection bias. The patient characteristics, operative procedures, surgical outcomes, oncologic and pathologic outcomes, number of lymph node dissections, quality of life assessment, and nutritional status were compared between the two groups. Results: After propensity score matching, 61 cases were included in the robotic group and 122 cases were included in the laparoscopic group. The number of dissected lymph nodes (37.3±13.5 vs. 32.8±11.8, P=0.022) was significantly differed between the two groups. The number of lower mediastinal and subphrenic lymph nodes in the robotic group was greater than that in the laparoscopic group, and the difference was statistically significant (P<0.001). Compared with the laparoscopic group, the total score of physical symptoms in the robotic group was significantly lower at 6 months and 12 months after surgery (P=0.03 and P=0.001, respectively). The total social function score at 6 months and 12 months after surgery was higher in the robotic group (P=0.006 and P=0.022). The quality of life scores were statistically significant only at 3 months after the operation (P=0.047). A higher PG-SGA score is, score significantly correlated (P<0.001) with a higher related physical symptoms score, lower social function score and lower quality of life score. Conclusion: Compared with laparoscopic radical gastrectomy, robotic radical gastrectomy is safe and feasible. Compared with laparoscopic radical gastrectomy, robotic radical gastrectomy was more refined, was associated with less surgical bleeding, and increased the quality of lymph node dissection. In addition, patients in the robotic group showed better postoperative quality of life.